Does Cueing Need Attention? A Pilot Study in People with Parkinson's Disease. (15th December 2022) - Silva-Batista, Carla; Miranda-Domínguez, Óscar; Ragothaman, Anjanibhargavi; Fair, Damien A.; Mantovani, Alessandra; Stuart, Sam; Nutt, John G.; Horak, Fay B.; Mancini, Martina
Highlights: Both open-loop and closed-loop cueing reduce freezing of gait. Responsiveness to both cueing in freezing of gait is unknown. Mechanisms underlying cueing responses are poorly understood. Brain networks predict responsiveness to open and closed-loop cueing. Salience network activity is a common predictor of responsiveness to both cueing. Abstract: We previously showed that both open-loop (beat of a metronome) and closed-loop (phase-dependent tactile feedback) cueing may be similarly effective in reducing Freezing of Gait (FoG), assessed with a quantitative FoG Index, while turning in place in the laboratory in a group of people with Parkinson's disease (PD). Despite the similar changes on the FoG Index, it is not known whether both cueing responses require attentional control, which would explain FoG Index improvement. The mechanisms underlying cueing responses are poorly understood. Here, we tested the hypothesis that the salience network would predict responsiveness ( i.e., FoG Index improvement) to open-loop and closed-loop cueing in people with and without FoG of PD, as salience network contributes to tasks requiring attention to external stimuli in healthy adults. Thirteen people with PD with high-quality imaging data were analyzed to characterize relationships between resting-state MRI functional connectivity and responses to cues. The interaction of the salience network and retrosplenial-temporal networks was the best predictor of responsiveness to open-loop cueing, presenting the largest effect size ( d = 1.16) . The interaction between the salience network and subcortical as well as cingulo-parietal and subcortical networks were the strongest predictors of responsiveness to closed-loop cueing, presenting the largest effect sizes ( d = 1.06 and d = 0.84, respectively). Salience network activity was a common predictor of responsiveness to both cueing, which suggests that auditory and proprioceptive stimuli during turning may require some level of cognitive and insular activity, anchored within the salience network, which explain FoG Index improvements in people with PD.